Static-to-Kinetic Solutions in Adaptive Reuse: Mechanisms for Transformation - Farmer, Theresa (University of Waterloo, 2025)
Public library branches stand as vital social infrastructure, yet their physical forms increasingly struggle to keep pace with technological, social, and environmental change. While their programs now support many different modes of making, learning, and gathering, the buildings remain static, limiting adaptability and user agency. Demolition and rebuilding are often treated as the only solutions, but such approaches are financially unsustainable and environmentally destructive, erasing buildings that embody local identity and collective memory. This thesis explores an alternative path: the use of responsive architectural additions that extend existing libraries without compromising their structural integrity or cultural meaning. It argues that preservation today must move beyond maintaining appearance or form toward sustaining continuity through active use and adaptation over time. Building on William Zuk and Roger H. Clark’s theory of kinetic architecture, the research explores a kinetic exhibition scaffold system composed of adjustable floors, walls, and furnishings as a way to achieve responsiveness and enable the public to shape and experience space. The Pleasant View Branch (1975) in Toronto, Canada, serves as the test site. The proposal introduces a lightweight overbuild addition, a new structure that appears to hover above the existing library while remaining structurally independent. This approach allows the original building to remain operational during construction, maintaining community access as transformation occurs above. Together, the elevated addition and reconfigurable interior scaffolding establish a practical model of adaptive reuse, where space can expand, contract, and transform in response to evolving patterns of use. The result is an extendable strategy for renewing the functional, civic, and environmental lifespan of public library branches without sacrificing the histories they hold.
Keywords: kinetic; library; adaptive reuse; social infrastructure; overbuild addition; user agency; scaffolding; Toronto public library